Mediation Effect of Knowledge Management Enablers on the Relationship between Organizational Characteristics and Entrepreneurial Orientation - Baskaran, Shathees (Gadjah Mada International Journal of Business, 2018)
The main aim of this study is to investigate the mediating effect of knowledge management enablers between the organizational characteristics and entrepreneurial orientation of employees. The study considered three constructs, namely: Knowledge management enablers, organizational characteristics and entrepreneurial orientation, to formulate the framework for this research. A quantitative approach was adopted in the study. Data were collected through a web-based online survey. The population of the survey was estimated to be around 300 employees from three cement manufacturing organizations in the state of Johor, Malaysia. A 70.4 per cent response rate was achieved. Five hypotheses were formulated and tested in the study. A simple multiple regression was used to analyse the data. All five hypotheses were supported, confirming that there is a partial mediation by the knowledge management enablers, as well as by the corresponding dimensions between organizational characteristics and entrepreneurial orientation. In addition, the implications of this study are also discussed, apart from the avenues for future research in the area of entrepreneurial orientation.